The tales of Beedle the Bard - Rowling, J. K. (Lumos, in association with Arthur A. Levine Books, 2017)
Contains five illustrated moral tales for children from the world of Harry Potter, reportedly discovered and translated by young witch Hermione Granger, with an introduction and commentary from Albus Dumbledore, headmaster of Hogwarts School of Witchcraft and Wizardry.